Determining appropriate government guarantees for concession contract: lessons learned from 10 PPP projects in China - Xu, Yelin; Yeung, John F. Y.; Jiang, Shaohua (International Journal of Strategic Property Management, 2014)
Governments worldwide are keen to encourage PPP schemes, however PPP is not a foolproof business. Many local governments and private investors have suffered severe or trying experiences. In this research, 10 case studies were conducted to identify the obstacles and difficulties for successful implementation of PPP projects from the perspective of government guarantees. These PPP projects include two water supply plants, two sewage treatment plants, two power supply plants, two highway projects, and two bridge projects. The findings obtained indicate that the local governments are familiar with “the type of guarantees” to provide to the private investor but they are unsure of the “amount” that should be given. Many PPP projects have therefore been heavily criticized for over benefiting the private investors as the government provides them with too many guarantees. The inappropriate guarantees offered by the government are regarded as one of the root causes of PPP projects’ failure. The lessons learned are valuable for determining appropriate government guarantees for future PPP projects and broadening the opportunities for infrastructure development with PPP procurement model. First Publish Online: 8 Dec 2014